The Concepts of Millenial Students Careing in Modern Boarding Schools - Abidah, Abidah; Razak, Abdul (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2023)
This paper aims to examine the concept of caring for millennial students in modern Islamic boarding schools. Along with the changing times experienced by Indonesian society, education in Islamic boarding schools has also developed. The research method used is literature review with a qualitative approach. From this research, it can be concluded that globalization in this millennial era has made their generation inseparable from the use of technology, the internet, social media and so on. This makes Islamic boarding schools modernize to meet the needs of this millennial generation community. Islamic boarding schools exist to provide better care for their millennial students. Various developments were carried out, including the integration of formal education and Islamic boarding schools, mastery of foreign languages, entrepreneurship, the use of information technology, various kinds of competitions and other training. This certainly has a positive impact on millennial students in dealing with changing times. Besides that, Islamic boarding schools must provide parenting support for students by giving freedom to students to act or be active in positive ways. Caregivers also provide supervision and direction and provide awards such as giving praise and motivation and even prizes, so that students continue to carry out activities that are even more developed. The rules and prohibitions on caregivers of students are also given a written explanation that is firm in nature, but their implementation is still flexible or is still tolerated. Furthermore, caregivers can also give freedom to students to do activities and make friends with anyone, but caregivers also carry out supervision and monitoring through senior students. Finally, caregivers provide motivations and advice and do not always comply with the wishes of students.